PERANCANGAN E-COMMERCE PADA ALL YOU CAN BUY BOUTIQUE JAMBI - Riza Anggi Wulandari; Jasmir; Lies Aryani (LPPM Universitas Dinamika Bangsa, 2023)
All You Can Buy Boutique Jambi is one of the company that moving at selling woman clothes product where the processes of promotion and sales still use manual way. So that problems occur is difficulty of increasing sales earnings with a big amount, a lack of facilities promotion which may be done by low cost , and a lack of facilities the provision of information the product offered. This research aims to design of e-commerce as a media promotion and sales of products. And this research using the PHP programming language, MySQL database, and waterfall for development system method. This research has stages such as identification problems, study of literature, gathering data, design system, development system, and making final reports. The result of this research is that this system is ease All You Can Buy Boutique Jambi in promoting with low cost, expanding the territory promotion and sales that can be inflated without having to awaiting customers come to the place